Comparison of Colour Duplex Ultrasound with Computed Tomography to Measure the Maximum Abdominal Aortic Aneurysmal Diameter. (23rd November 2014) - Gray, C.; Goodman, P.; Badger, S. A.; O'Malley, M. K.; O'Donohoe, M. K.; McDonnell, C. O.
Abstract : Introduction . Maximum diameter of an abdominal aortic aneurysm (AAA) is the main indication for surgery. This study compared colour duplex ultrasound (CDU) and computed tomography (CT) in assessing AAA diameter. Patients and Methods . Patients were included if they had both scans performed within 90 days. Pearson's correlation coefficient, paired t -test, and limits of agreement (LOA) were calculated for the whole group. Subgroup analysis of small (<5.0 cm), medium (5.0–6.5 cm), and large (>6.5 cm) aneurysms was performed. A P value of <0.05 was considered statistically significant. Results . 389 patients were included, giving 130 pairs of tests for comparison. Excellent correlation was in the whole group ( r = 0.95) and in the subgroups ( r = 0.94; 0.69; 0.96, resp.). Small LOA between the two imaging modalities was found in all subgroups. Conclusion . Small aneurysms can be accurately measured using CDU. CDU is preferable for small AAAs, but cannot supplant CT for planning aortic intervention.